MODIFIKASI METODE HALLEY BERDASARKAN METODE OSADA DAN EULER CHEBYSHEV UNTUK AKAR GANDA - Romendiana '; Imran M.; Bustami ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
In this article discusses the modification of Halley’s method to solve nonlinear equa-tions having multiple roots. The method is obtained using improvements of the Osada’s method and Euler-Chebyshev’s method. Analytically , we show that this iterative method have third order for a multiple roots. Furthermore, numerical ex-periments show that, the modification of Halley method is superior to Newton’smethod for multiple roots.